Interlimb Dynamic after Unilateral Focal Lesion of the Cervical Dorsal Corticospinal Tract with Endothelin-1 - Carvalho, Walther A.; Bahia, Carlomagno P.; Teixeira, Jéssica C.; Gomes-Leal, Walace; Pereira, Antonio (Frontiers in Neuroanatomy, 2017)
Handedness is one of the most recognized lateralized behavior in humans. Usually, it is associated with manual superiority regarding performance proficiency. For instance, more than 90% of the human population is considered more skilled with the right hand, which is controlled by the left hemisphere, than with the left. However, during the performance of bimanual tasks, the two hands usually assume asymmetric roles, with one hand acting on objects while the other provides support, stabilizing the object. Traditionally, the role of the two hands is viewed as fixed. However, several studies support an alternate view with flexible assignments for the two hands depending on the task. The supporting role of the hand depends on a closed loop pathway based on proprioceptive inputs from the periphery. The circuit’s efferent arm courses through the dorsal corticospinal tract (dCST) in rodents and terminate on spinal cord interneurons which modulate the excitability of motoneurons in the ventral horn. In the present work, we developed an experimental model of unilateral lesion targeting the cervical dCST with microinjections of the vasoconstrictor endothelin-1 (ET-1) to evaluate the degree of flexibility of forelimb assignment during a food manipulation task. Our results show that just three days after unilateral CST injury in the cervical region, rats display severe motor impairment of the ipsilateral forepaw together with a remarkable reversal of motor assignment between the forelimbs.